MRS Reveals Chronic Inflammation in T2w MRI-Negative Perilesional Cortex – A 6-Months Multimodal Imaging Follow-Up Study - Yasmin, Amna; Pitkänen, Asla; Jokivarsi, Kimmo; Poutiainen, Pekka; Gröhn, Olli; Immonen, Riikka (Frontiers in Neuroscience, 2019)
Sustained inflammation in the injured cortex is a promising therapeutic target for disease-modification after traumatic brain injury (TBI). However, its extent and dynamics of expansion are incompletely understood which challenges the timing and placement of therapeutics to lesioned area. Our aim was to characterize the evolution of chronic inflammation during lesion expansion in lateral fluid-percussion injury (FPI) rat model with focus on the MRI-negative perilesional cortex. T2-weighted MR imaging (T2w MRI) and localized magnetic resonance spectroscopy (MRS) were performed at 1, 3, and 6 months post-injury. End-point histology, including Nissl for neuronal death, GFAP for astrogliosis, and Prussian Blue for iron were used to assess perilesional histopathology. An additional animal cohort was imaged with a positron emission tomography (PET) using translocator protein 18 kDa (TSPO) radiotracer [18F]-FEPPA. T2w MRI assessed lesion growth and detected chronic inflammation along the lesion border while rest of the ipsilateral cortex was MRI-negative (MRI-). Instead, myoinositol that is an inflammatory MRS marker for gliosis, glutathione for oxidative stress, and choline for membrane turnover were elevated throughout the 6-months follow-up in the MRI- perilesional cortex (all p < 0.05). MRS markers revealed chronically sustained inflammation across the ipsilateral cortex but did not indicate the upcoming lesion expansion. Instead, the rostral expansion of the cortical lesion was systematically preceded by a hyperintense band in T2w images months earlier. Histologic analysis of the hyperintensity indicated scattered astrocytes, incomplete glial scar, and intracellularly packed and free iron. Yet, the band was negative in [18F]-FEPPA-PET. [18F]-FEPPA also showed no cortical TSPO expression within the MRS voxel in MRI- perilesional cortex or anywhere along glial scar when assessed at 2 months post-injury. However, [18F]-FEPPA showed a robust signal increase, indicating reactive microgliosis in the ipsilateral thalamus at 2 months post-TBI. We present evidence that MRS reveals chronic posttraumatic inflammation in MRI-negative perilesional cortex. The mismatch in MRS, MRI and PET measures may allow noninvasive endophenotyping of beneficial and detrimental inflammatory processes to aid targeting and timing of anti-inflammatory therapeutics.